2016
DOI: 10.1186/s13046-016-0353-8
|View full text |Cite|
|
Sign up to set email alerts
|

Combined therapy with oncolytic adenoviruses encoding TRAIL and IL-12 genes markedly suppressed human hepatocellular carcinoma both in vitro and in an orthotopic transplanted mouse model

Abstract: BackgroundGene-based virotherapy mediated by oncolytic viruses is currently experiencing a renaissance in cancer therapy. However, relatively little attention has been given to the potentiality of dual gene virotherapy strategy as a novel therapeutic approach to mediate triplex anticancer combination effects, particularly if the two suitable genes are well chosen. Both tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) and interleukin-12 (IL-12) have been emerged as promising pharmacological candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 46 publications
(101 reference statements)
0
42
0
1
Order By: Relevance
“…Despite the development of various modalities for the treatment of HCC, such as surgical resection, radio frequency ablation, transcatheter arterial chemoembolization, and systemic chemotherapy, the prognosis of patients with HCC is still poor . A novel therapeutic strategy is therefore required to treat such patients; in order to fulfill this need, gene therapy has received much attention …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the development of various modalities for the treatment of HCC, such as surgical resection, radio frequency ablation, transcatheter arterial chemoembolization, and systemic chemotherapy, the prognosis of patients with HCC is still poor . A novel therapeutic strategy is therefore required to treat such patients; in order to fulfill this need, gene therapy has received much attention …”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have evaluated the effects of gene therapies for the treatment of HCC; some of these have reached clinical phases . Gendicine, which consists of adenoviral vectors and a normal copy of the p53 tumor suppressor gene, was the first commercially licensed gene therapy drug .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this study documented a remarkable suppression of VEGF with infiltration of natural killer cells (NK cells) and antigen-presenting cells (APCs) at tumor microenvironment (TME). Moreover, enhanced apoptosis and upregulation of interferon- γ (IFN- γ ) production were also reported in this study [73]. In addition, a combination of doxorubicin with α -fetoprotein- (AFP-) E1A-IRES-E1B bicistronic cassette derived from Ad5, CV890 showed a synergic antitumor effect in vitro as well as in vivo [74].…”
Section: Oncolytic Virus-based Preclinical Studiesmentioning
confidence: 53%
“…The anticancer therapeutic potential of OAd virotherapy strategy-mediated co-delivery of TRAIL and IL-12 genes has not been sufficiently investigated thus far. El-Shemi et al (79) suggested in their preclinical study that dual therapy with Ad-ΔB/TRAIL plus Ad-ΔB/IL-12 markedly suppressed human HCC via the promotion of antitumor apoptosis and immune activity, as well as by inhibiting tumor angiogenesis and neovascularization. Although further studies are warranted to evaluate this therapeutic combination, and also to explore the precise anti-tumor mechanisms, the OAd strategy-mediated co-delivery of TRAIL and IL-12 genes may be a potential therapeutic strategy for the treatment of human HCC, along with other types of cancer (79).…”
Section: New Trends In Ov Based Approachesmentioning
confidence: 99%
“…El-Shemi et al (79) suggested in their preclinical study that dual therapy with Ad-ΔB/TRAIL plus Ad-ΔB/IL-12 markedly suppressed human HCC via the promotion of antitumor apoptosis and immune activity, as well as by inhibiting tumor angiogenesis and neovascularization. Although further studies are warranted to evaluate this therapeutic combination, and also to explore the precise anti-tumor mechanisms, the OAd strategy-mediated co-delivery of TRAIL and IL-12 genes may be a potential therapeutic strategy for the treatment of human HCC, along with other types of cancer (79). Co-therapy with OAd-expressing TRAIL and another type of immunostimulant cytokine (IL-24) has been previously reported to be associated with potent activation in the caspase pathway, particularly of caspases-3 and -8, and apoptosis promotion in HCC (80).…”
Section: New Trends In Ov Based Approachesmentioning
confidence: 99%